If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(12y-5=)
We move all terms to the left:
(12y-5-())=0
We calculate terms in parentheses: +(12y-5-()), so:y=0/12
12y-5-()
We add all the numbers together, and all the variables
12y
Back to the equation:
+(12y)
y=0
| -4(3x+1)=8x-2 | | 2x+3(-x-5)=-10 | | 12=3(x−2) | | q+|3|=-5 | | 1y+1y-1=11 | | (16x+21=) | | 0.3x+1.2=0.7x-2.0 | | 4n+5=4n+3 | | U=4K/a | | 6+4c=2 | | n^2-7n-5=3 | | 5⁄6x=15 | | 10+8=-2(8x+9) | | 3(x-2+x-1=5 | | |2x+5|-2=10 | | 14+11-9m=1+4m-7 | | 2x+38=X+30 | | |2u-1|=15 | | b/2-5=7 | | −2(7−y)+4=−4 | | 5(3x+7)=13 | | (1/7)-2b=7 | | 5x+12=-5x+7 | | 3(5x+7)=-16+7 | | 5/3/1/5=20/30/e | | 3(x+9)=8x+6-5x+21 | | 8p+7=7p+8 | | d+20/8=5 | | 4+16y=9 | | -7r=9.1r-7.56 | | 3(2x+7)=-18+15 | | 66x+207=−4x+12 |